Abu Al-Hasan 'Ali Al-Hasani An-Nadwi: Keperibadian, Sejarah Hidup dan Perjuangan - Zamzam, Ahmad Fahmi (Jurnal Usuluddin, 2000)
Al-Nadwi's personality, life and his efforts for the development of Islam are discussed. It also deals with his masterpieces, his involvement in Islamic movements and his journey. His relation and admiration of lqbal is also been described briefly.